Never trust a dead man - Vande Velde, Vivian (San Diego : Harcourt Brace, 1999)
Wrongly convicted of murder and punished by being sealed in the tomb with the dead man, seventeen-year-old Selwyn enlists the help of a witch and the resurrected victim to find the true killer.
Keywords: Murder -- Fiction; Mystery and detective stories